Analisis Pemasaran Sosial Media Melalui Perkembangan Teknologi Terhadap Produk Smartwatch - Siti Aisyah; Rohmawati Rohmawati; Eli Masnawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Something that is quite significant about smartwatches today is their role in helping users monitor health and fitness, by carrying various superior features ranging from measuring heart rate, measuring oxygen pressure in the blood, footsteps, running distance, GPS features, calculating sleep hours, notifications. cell phone, music settings and answering incoming calls. What is no less interesting about smartwatches is that their internal devices are very modern for users ranging from teenagers to adults. This research was carried out through monitoring social media and conducting research in the research office area located in Ruko Apartment Puncak Bukit Golf No. 1. The influence of using social media is sufficient to function as an effective platform for promoting smartwatch products, which provides direct interaction between sellers and buyers.